Dual-Purpose Cover Crop Effects on Soil Health in Western Kansas No-Till Dryland Cropping - L. M. Simon; A. K. Obour; J. D. Holman; S. K. Johnson; K. L. Roozeboom (Kansas Agricultural Experiment Station Research Reports, 2021)
Increasing interest in soil health has led producers in western Kansas to consider cover crops (CCs) for increased soil cover and improved soil properties. However, grain yield reductions following CCs in dryland cropping systems necessitate dual-purpose forage harvest to balance goals of environmental and economic sustainability. This study was initiated in 2015 near Brownell, KS, to investigate the effects of dual-purpose CC management in place of fallow on selected soil chemical and physical properties in a no-till winter wheat-grain sorghum-fallow cropping system. Mixed oat and triticale cover crops were either mechanically harvested as hayed forage to a height of 6 inches, mob-grazed with yearling heifers (weighing approximately 1000 lb each) stocked at 3 head/acre/day, or left standing (unharvested). Cover crop treatments were compared to chemically-controlled no-till fallow. Soil samples were collected following CC termination, but before winter wheat planting in 2019 and 2020. Results indicate that dual-purpose CCs had no effect on soil bulk density or porosity relative to unharvested CCs or the fallow treatment. Soil organic carbon was similar for standing and grazed CCs though carbon stocks were less for the hayed treatment. All CC treatments were similar to fallow. Indicators of soil structure—including mean weight diameter and large macroaggregates—were greater, while small macroaggregates were less for all CCs compared to fallow. These results suggest that dual-purpose CCs in no-till dryland cropping may replace fallow to provide forage for livestock while improving soil health. Still, careful management will be necessary to ensure adequate CC residues are retained such that, when CC growth is limited, grazing of CCs may be more desirable than haying in order to maintain soil properties.
Keywords: cover crops; dryland; grazing; soil health